1998
DOI: 10.1111/j.1502-3931.1998.tb00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of Early Paleozoic trilobites

Abstract: Asymmetry in fossils can arise through a variety of biological and geological mechanisms. If geological sources of asymmetry can be minimized or factored out, it might be possible to assess biological sources of asymmetry. Fluctuating asymmetry (FA), a general measure of developmental precision, is documented for nine species of lower Paleozoic trilobites. Taphonomic analyses suggest that the populations studied for each taxon span relatively short time intervals that are approximately equal in duration. Tecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…). Such fluctuating asymmetry was already demonstrated by Smith () on linear measurements on early Cambrian trilobites, suggesting that early trilobites possessed genetic or developmental mechanisms comparable to those of younger trilobites.…”
Section: Relation Between Development and Evolutionsupporting
confidence: 60%
“…). Such fluctuating asymmetry was already demonstrated by Smith () on linear measurements on early Cambrian trilobites, suggesting that early trilobites possessed genetic or developmental mechanisms comparable to those of younger trilobites.…”
Section: Relation Between Development and Evolutionsupporting
confidence: 60%
“…Smith [295] studied asymmetry in nine genera of early Paleozoic (lower Cambrian through Silurian) trilobites (Trilobita: Arthropoda). The idea that the Cambrian Explosion was due, in part, to lax developmental constraints suggested that fluctuating asymmetry might decline through the Paleozoic.…”
Section: Fossil Materialsmentioning
confidence: 99%
“…There are few studies applying the FAlhomozygosity correlation to the fossil record (see review in Palmer 1986). However, several examples include the examination of FA in Pliocene horses (Van Valen 1962), the analysis of patterns of antisymmetry in Jurassic brachiopods (Fursich &Palmer 1984), the measurement of FA in lower Paleozoic trilobites (Smith 1998), and the study of dental anomalies in upper Eocene anthracoteriids related to inbreeding (Ducrocq et al 1995).…”
Section: Cranial Fluctuating Asymmetry: Implications For Developmentamentioning
confidence: 99%